Lower Triassic Antarctic vertebrate fossils at Field Museum, Chicago, IL - Makovicky, Peter (U.S. Antarctic Program (USAP) Data Center, 2022)
Spreadsheet with provisional taxonomic identification and locality data for Early Triassic vertebrate fossils from the Allen Hills region accessioned at Field Museum, Chicago, IL